Man and His Migrations - Latham, R. G. (Robert Gordon), 1812-1888 (Salt Lake City, UT : Project Gutenberg, 2014)
"Man and His Migrations" by R. G. Latham is a scientific publication written in the mid-19th century. The work presents a series of lectures exploring the natural and physical history of mankind, focusing on topics such as anthropology, ethnology, and the factors influencing human migrations across different geographies. Latham delves into the evolution, characteristics, and classifications of various human populations, seeking to understand how humans have historically spread and adapted to diverse environments. The opening portion of the book sets the stage for a comprehensive analysis of the natural history of man, contrasting it with civil history. Latham discusses the significance of anthropology and ethnology, defining them and outlining their roles in understanding human diversity and migration. He highlights the limitations of ancient and modern studies in these fields, referencing notable historical figures and their contributions. Furthermore, he poses critical questions related to the origins and classifications of humans, suggesting that understanding these aspects is crucial for grasping the dynamics of human populations and their movements throughout history. Overall, this portion serves as an introduction to the broader inquiry that follows about the human species and its migration patterns. (This is an automatically generated summary.)
Release date is 2014-01-06
E-text prepared by Colin Bell, Marie Bartolo, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Ethnology; Human beings -- Migrations